2021
DOI: 10.1186/s43055-021-00426-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of MDCT in the assessment of cardiac and extra-cardiac vascular defects among Egyptian children with tetralogy of Fallot and its surgical implementation

Abstract: Background Tetralogy of Fallot (TOF) is considered the most common form of cyanotic congenital heart diseases (CHD), accounting for about 10% of cases. It includes four main cardiac defects, in addition to various extra-cardiac anomalies. Aim This study aimed to evaluate cardiac and extra-cardiac vascular defects associated with TOF among Egyptian children, regarding frequency and types with assessment of multi-slice or multi-detector computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…Six patients (20 percent) were found to have coronary artery abnormalities in our study. These findings similar to Elshimy et al [23], Hrusca et al [13] who reported anomalies of coronary artery incidence (20 % and 22.85% respectively). However, this disagrees with Sheikh et al [16] who detected coronary artery anomalies in 4.9 % of cases, and Shehata et al [11] who reported coronary artery irregularities in 3.3% of cases.…”
Section: Discussionsupporting
confidence: 90%
“…Six patients (20 percent) were found to have coronary artery abnormalities in our study. These findings similar to Elshimy et al [23], Hrusca et al [13] who reported anomalies of coronary artery incidence (20 % and 22.85% respectively). However, this disagrees with Sheikh et al [16] who detected coronary artery anomalies in 4.9 % of cases, and Shehata et al [11] who reported coronary artery irregularities in 3.3% of cases.…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed that MDCT could identify the exact origin and course in all cases while echo was unable to identify proximal course abnormalities, this agreed with Nie et al (21) who found that MSCT displayed the origin and course of all anomalous vessels with 100% sensitivity. And also close to Bu et al (3) , Shehata et al (12) and Elshimy et al (22) who showed that MDCT was superior to TTE in diagnosing Anomalous origin of coronary artery.…”
Section: Discussionsupporting
confidence: 72%